(untitled) (Agroindustria, Sociedad y Ambiente, 2024)
The evaluation of quail eggs under the effect of the use of vitamins in the first phase of production was developed in the province of Morona Santiago at an altitude of 1160 meters above sea level, a temperature between 16 - 24 ºC and a precipitation of 63 - 122 mm of rain/month; the place where the 16 cages with 8 birds were placed, distributed in 4 treatments (Vitamin B + ADE, Vitamins ADE and Vitamin B complex versus a control treatment) and 4 replicates. The experimental results were analyzed under the additive linear model Yij = u + Ti + Eij. It was determined that the application of vitamins in the quails allowed the recording of eggs with a transverse diameter of 2.53±0.08 to 2.68±0.09 cm, lungitudinal diameter of 3.16±0.13 to 3.30±0.07 cm, a weight between 11.44±1, 21 to 12.24±1.33 g, a volume between 10.83±1.03 to 11.17±1.19 ml, a bulk density between 1.07±0.06 to 1.10±0.04 g/l, a shell thickness between 0.25±0.04 and 0.28±0.03 mm, characteristics that were not influenced by vitamins. While the weight of the shell with the control treatment was 1.64±0.17 g and the weight of the yolk + albumin was 10.87±0.64 g, being superior to the rest of the treatments. When analyzing between the yolk and albumin of the quail egg, the pH of the albumin was alkaline while that of the yolk was acidic, likewise it is more turbid, contains reducing sugars, a higher density, dry matter, organic matter, although ash is found in smaller proportion, concluding that it is not necessary to include additional vitamins to those available in the food, since it does not influence the physical characteristics of quail eggs.